Law Enforcement Through Criminal Sanctions for Employers' Violations of Workers' Wages in Indonesia - D. Andry Effendy; Faisal Santiago (International Journal Labs, 2023)
Wages are a form of appreciation given by employers for the services that have been done by workers. Wages are able to ensure the welfare of workers. However, in reality there are still wage violations in Indonesia, such as in terms of nominal wages. Nominal wages that are not in accordance with the provisions will interfere with worker welfare and reduce worker productivity. Wages must be guaranteed by law so that the essence of the function of wages can be realized. Therefore, research is needed on criminal sanctions as law enforcement of employers' violations of workers' wages in Indonesia. The objectives of this study include (1) explaining the forms of employer violations against workers' wages in Indonesia and (2) explaining the forms of criminal sanctions for employers' violations of workers' wages as an effort to enforce the law in Indonesia. This research is based on qualitative and uses an analytical descriptive approach, and is normative juridical. Forms of employer violations against workers' wages in Indonesia consist of nominal wage violations, late payment of workers' wages, and employers' unwillingness to pay workers' wages. Criminal sanctions as an effort to enforce the law are realized through Government Regulation in Lieu of Law of the Republic of Indonesia Number 2 of 2022 concerning Job Creation paragraphs (1) and (2) for violations in the event that the nominal wage is less than the provisions. The forms of violations of late payment of wages and the unwillingness of employers to pay workers' wages are subject to criminal sanctions listed in paragraph 61 paragraph (1) of Government Regulation (PP) concerning Wages.